Synthesis, photoluminescence properties and energy transfer behavior of color-tunable fluorapatite phosphor Sr9Gd(PO4)5(SiO4)F2:Tb3+/Sm3+. Issue 15 (15th November 2016) - Liu, Haikun; Liao, Libing; Yang, Dan; Guo, Qingfeng; Mei, Lefu
Abstract: Tb 3+ -Sm 3+ co-doped Sr9 Gd(PO4 )5 (SiO4 )F2 (SGPSF) phosphors were prepared through a solid-state reaction, and their luminescence properties as well as energy transfer mechanism have been investigated in detail. The SGPSF:Tb 3+, Sm 3+ phosphors system could be efficiently excited at wavelengths ranging from 200 to 500 nm, which is well matched with the spectra of near ultraviolet chips. The emission of SGPSF:Tb 3+, Sm 3+ phosphor covers the entire visible region with sharp peaks in the blue, green, and red regions. The emission color of SGPSF:Tb 3+, Sm 3+ could be adjusted from green (0.275, 0.378) to red (0.519, 0.295) by controlling the doping content of Sm 3+ /Tb 3+ .